1989
DOI: 10.1136/gut.30.9.1213
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharidase activity in the small intestine of gerbils (Meriones unguiculatus) during primary and challenge infections with Giardia lamblia.

Abstract: SUMMARY The sequence of changes in the activity of six disaccharidases in the small intestine of gerbils during primary and secondary G lamblia infections was examined. The primary G lamblia infection induced a transient reduction in disaccharidase activity which was related to the highest trophozoite burden in the small intestine. During the primary exposure, a 30% to 85% decrease in the activity of enzymes was observed on days 10 and 20 after infection. Secondary exposure of gerbils to G lamblia caused a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 17 publications
7
33
0
Order By: Relevance
“…The present in vivo study consolidates recent reports describing the capacity of some lactobacilli of human and canine origin to antagonize Giardia infection which interferes with the growth and cell cycle of G. intestinalis in vitro (36). Mongolian gerbils (Meriones unguiculatus) are a good animal model for studying Giardia infection with strains of human origin (3,4,11). Their susceptibility to giardiasis has been attributed to a deficient antibody response to specific Giardia antigens (34).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The present in vivo study consolidates recent reports describing the capacity of some lactobacilli of human and canine origin to antagonize Giardia infection which interferes with the growth and cell cycle of G. intestinalis in vitro (36). Mongolian gerbils (Meriones unguiculatus) are a good animal model for studying Giardia infection with strains of human origin (3,4,11). Their susceptibility to giardiasis has been attributed to a deficient antibody response to specific Giardia antigens (34).…”
supporting
confidence: 82%
“…Intestinal disaccharidase activity was determined as previously reported (16). Protein concentrations were determined using the Bradford assay, and the results are expressed as arbitrary units per gram of protein (3).…”
mentioning
confidence: 99%
“…First, in immuno-competent but not in T-cell deficient animals, acute giardiasis causes a diffuse loss of epithelial brush border surface area and decreases sucrase and maltase activities (Scott et al 2000). During the acute phase of the infection, epithelial abnormalities were not seen in the jejunum of Gupta et al 1973, Chawla 1975, Ducombe et al 1978, Gillon et al 1982, Faubert 1988, Belosevic et al 1989, 1992, Favennec et al 1991, Katelaris et al 1991, Cevallos et al 1995, Mohammed et al 1995, O'Handley et al 2001 athymic mice, despite comparable parasitic loads to those seen in immuno-competent animals, implying that the lack of microvillous injury could not be attributed to a reduction in trophozoite numbers. Second, experiments using in vivo T lymphocyte transfer into naïve animals demonstrate that brush border injury and malfunction in giardiasis are mediated by CD8 + T lymphocytes, while CD4 + T lymphocytes are responsible for parasite clearance (Scott et al 2004).…”
Section: The Role Of Cd8 + Lymphocytes In Pathogenesismentioning
confidence: 99%
“…Recent studies have found that CD8+ lymphocyte adhesion to epithelial cells via α E β 7 contributes to the destruction of pancreatic islet cells (Butcher et al 1996, Feng et al 2002. Previous reports have also shown that secondary challenge with fractions of G. duodenalis trophozoites may cause disaccharidase deficiencies in the absence of live parasites (Belosevic et al 1989). The signaling events implicating CD8 + T cells, integrins like α E β 7, and possibly TGFβ , in the brush border injury during giardiasis and other disorders of the intestine warrant further investigations.…”
mentioning
confidence: 99%
“…Studies in human patients, in experimental animal models, or in cell culture systems, have established that the infection causes small intestinal structural and functional abnormalities. These may include apoptosis induced epithelial barrier defects, microvillous shortening, disaccharidase deficiencies, hypersecretion of chloride, as well as malabsorption of electrolytes and water associated with infiltration of intraepithelial lymphocytes ( [Belosevic et al, 1989], [Buret et al, 1992], [Scott et al, 2000], , [Scott et al, 2004], [Troeger et al, 2007] and [Panaro et al, 2007]). …”
Section: Introductionmentioning
confidence: 99%